2006
DOI: 10.1074/jbc.m512080200
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroid Phenotype Is Contributed by Mitochondrial Complex I Inactivation Due to Translocated Neuronal Nitric-oxide Synthase

Abstract: Although transcriptional effects of thyroid hormones have substantial influence on oxidative metabolism, how thyroid sets basal metabolic rate remains obscure. Compartmental localization of nitric-oxide synthases is important for nitric oxide signaling. We therefore examined liver neuronal nitric-oxide synthase-␣ (nNOS) subcellular distribution as a putative mechanism for thyroid effects on rat metabolic rate. At low 3,3 ,5-triiodo-L-thyronine levels, nNOS mRNA increased by 3-fold, protein expression by one-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
70
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 52 publications
(52 reference statements)
13
70
0
1
Order By: Relevance
“…In addition, new isoforms or mitochondrial variants of NOS (mtNOS) have since been described in rat liver (Ghafourifar and Richter, 1997;Giulivi et al, 1998), thymus (Bustamante et al, 2000), and brain (Riobo et al, 2002). mtNOS is bound to mitochondrial cytochrome c oxidase (COX) (Persichini et al, 2005) and to complex I (Franco et al, 2006), thus favoring a steric relationship between the released NO and the control of respiration. NO is critical for numerous biological processes, including PCD, and it functions through both cGMPdependent and-independent pathways.…”
Section: No Production In Mammalian and Plant Cellsmentioning
confidence: 99%
“…In addition, new isoforms or mitochondrial variants of NOS (mtNOS) have since been described in rat liver (Ghafourifar and Richter, 1997;Giulivi et al, 1998), thymus (Bustamante et al, 2000), and brain (Riobo et al, 2002). mtNOS is bound to mitochondrial cytochrome c oxidase (COX) (Persichini et al, 2005) and to complex I (Franco et al, 2006), thus favoring a steric relationship between the released NO and the control of respiration. NO is critical for numerous biological processes, including PCD, and it functions through both cGMPdependent and-independent pathways.…”
Section: No Production In Mammalian and Plant Cellsmentioning
confidence: 99%
“…There exist three canonical isoforms [neuronal (NOS I or nNOS), inducible (NOS II), and endothelial (NOS III)] and a significant number of spliced and posttranslationally modified variants. In addition, new isoforms or mitochondrial variants of NOS (mtNOS) were recently described in rat liver (60,63), thymus (29), and brain (119); mtNOS is bound to mitochondrial PDZ domains of COX (57,103) and to complex I (57), thus favoring a steric relationship between the released NO, vectorially directed to the matrix and inner membrane, and the control of respiration. In pathological conditions such as extreme hypoxia, mitochondrial NO could come either from stimulated NOS (116,142) or from the reduction of nitrite by COX (39).…”
Section: Nitric Oxide In Mitochondriamentioning
confidence: 99%
“…In addition, new isoforms or mitochondrial variants of NOS (mtNOS) were recently described in rat liver (Ghafourifar and Richter, 1997;Giulivi et al, 1998), thymus (Bustamante et al, 2000) and brain (Riobo et al, 2002). It was previously reported that mtNOS forms complexes with mitochondrial COX (Persichini et al, 2005;Franco et al, 2006) and complex I (Franco et al, 2006), thus favoring a steric relationship of newly synthesized NO to the control of mitochondrial-dependent respiration reaction. Interestingly, the mtNOS had been reported to be a NOS1 isoform that is translocated to mitochondria.…”
Section: Discussionmentioning
confidence: 99%